"슬레이터 1"의 두 판 사이의 차이
둘러보기로 가기
검색하러 가기
27번째 줄: | 27번째 줄: | ||
* Use the following<br><math>\delta_n=\frac{(y)_n(z)_n x^n}{y^n z^n}</math>, <math>\gamma_n=\frac{(x/y;q)_{\infty}(x/z;q)_{\infty}}{(x;q)_{\infty}(x/yz;q)_{\infty}}}\frac{(y)_n(z)_n x^n}{(x/y)_{n}(x/z)_{n}y^n z^n}=\frac{(x/y;q)_{\infty}(x/z;q)_{\infty}}{(x;q)_{\infty}(x/yz;q)_{\infty}}}\frac{\delta_{n}}{(x/y)_{n}(x/z)_{n}}</math><br> | * Use the following<br><math>\delta_n=\frac{(y)_n(z)_n x^n}{y^n z^n}</math>, <math>\gamma_n=\frac{(x/y;q)_{\infty}(x/z;q)_{\infty}}{(x;q)_{\infty}(x/yz;q)_{\infty}}}\frac{(y)_n(z)_n x^n}{(x/y)_{n}(x/z)_{n}y^n z^n}=\frac{(x/y;q)_{\infty}(x/z;q)_{\infty}}{(x;q)_{\infty}(x/yz;q)_{\infty}}}\frac{\delta_{n}}{(x/y)_{n}(x/z)_{n}}</math><br> | ||
− | * Specialize<br><math>x=q | + | * Specialize<br><math>x=q, y\to\infty, z\to\infty</math>.<br> |
− | * Bailey pair<br><math>\delta_n= | + | * Bailey pair<br><math>\delta_n=q^{n^2}</math><br><math>\gamma_n=\frac{(-q)_{\infty}}{(q^2)_{\infty}}q^{\frac{n(n+1)}{2}}</math><br> |
− | |||
− | |||
2011년 11월 14일 (월) 10:32 판
이 항목의 수학노트 원문주소
노트
항등식의 종류
켤레 베일리 쌍의 유도
- Use the following
\(\delta_n=\frac{(y)_n(z)_n x^n}{y^n z^n}\), \(\gamma_n=\frac{(x/y;q)_{\infty}(x/z;q)_{\infty}}{(x;q)_{\infty}(x/yz;q)_{\infty}}}\frac{(y)_n(z)_n x^n}{(x/y)_{n}(x/z)_{n}y^n z^n}=\frac{(x/y;q)_{\infty}(x/z;q)_{\infty}}{(x;q)_{\infty}(x/yz;q)_{\infty}}}\frac{\delta_{n}}{(x/y)_{n}(x/z)_{n}}\) - Specialize
\(x=q, y\to\infty, z\to\infty\). - Bailey pair
\(\delta_n=q^{n^2}\)
\(\gamma_n=\frac{(-q)_{\infty}}{(q^2)_{\infty}}q^{\frac{n(n+1)}{2}}\)
베일리 쌍의 유도
- Use the following
\(\sum_{r=0}^{n}\frac{(1-aq^{2r})(-1)^{r}q^{\frac{1}{2}(r^2+r)}(a)_{r}(c)_{r}(d)_{r}a^{r}}{(a)_{n+r+1}(q)_{n-r}(q)_{r}(aq/c)_{r}(aq/d)_{r}c^{r}d^{r}}=\frac{(aq/cd)_{n}}{(q)_{n}(aq/c)_{n}(aq/d)_{n}}\) - Specialize
\(a=1,c=0,d=\infty\) - Bailey pair
\(\alpha_{0}=1\), \(\alpha_{r}=(-1)^{r}(1+q^r)q^{\frac{1}{2}r(r-1)}\)
\(\beta_{0}=1\), \(\beta_{r}=0\)
\(\beta_n=\sum_{r=0}^{n}\frac{\alpha_r}{(x)_{n-r}(q)_{n+r}}=\sum_{r=0}^{n}\frac{(-1)^{r}(1+q^r)q^{\frac{1}{2}r(r-1)}}{(q)_{n-r}(q)_{n+r}}=0\)